2020
DOI: 10.3390/ijms21082877
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Role of Melatonin in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an inflammatory joint disorder characterized by synovial proliferation and inflammation, with eventual joint destruction if inadequately treated. Modern therapies approved for RA target the proinflammatory cytokines or Janus kinases that mediate the initiation and progression of the disease. However, these agents fail to benefit all patients with RA, and many lose therapeutic responsiveness over time. More effective or adjuvant treatments are needed. Melatonin has shown beneficial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…The levels of tissue lipid peroxidation and reduced glutathione were also brought back to that seen in control animals by continued melatonin treatment [45]. Melatonin, by suppressing the activity of M1 subtype macrophages, reduced inflammation [72] even evoked by autoimmunity [75]. It appears that ISO-induced oxidative stress and inflammation were suppressed by treatment with melatonin and omega-3 as both exert powerful anti-oxidants and anti-inflammatory properties [67,74].…”
Section: Discussionmentioning
confidence: 86%
“…The levels of tissue lipid peroxidation and reduced glutathione were also brought back to that seen in control animals by continued melatonin treatment [45]. Melatonin, by suppressing the activity of M1 subtype macrophages, reduced inflammation [72] even evoked by autoimmunity [75]. It appears that ISO-induced oxidative stress and inflammation were suppressed by treatment with melatonin and omega-3 as both exert powerful anti-oxidants and anti-inflammatory properties [67,74].…”
Section: Discussionmentioning
confidence: 86%
“…Melatonin is one of the major neuroendocrine hormones that show a remarkable functional versatility. Indeed, although its primary function consists of the regulation of circadian rhythm, melatonin also promotes mitochondrial homeostasis, proliferation, apoptosis, metastasis, oncostatic, anti-aging, antioxidant, and immunomodulatory properties [ 62 , 63 , 83 ].…”
Section: Tryptophan Metabolism and Ramentioning
confidence: 99%
“…Therefore, on one hand, several researches suggest that melatonin may enhance pro-inflammatory activities and promote disease activity in RA, while, on the other, other preclinical and clinical investigations document substantial anti-inflammatory and immunoregulatory properties of melatonin in the same disease [ 83 ]. Some investigators have suggested that melatonin could be effective as adjunctive therapy in the treatment of RA [ 96 ].…”
Section: Tryptophan Metabolism and Ramentioning
confidence: 99%
“…Although the reports regarding effects of melatonin on autoimmune inflammation are not consistent, its potential beneficial effects in this condition have drawn a great attention recently. For example, recent evidence has demonstrated that melatonin down-regulates MMP9 activity, as well as IL-1β and TNF-α expressions in the synovial fibroblasts of patients with rheumatoid arthritis (RA) (167). Melatonin also stimulates microRNA (miR-3150a-3p) to produce anti-apoptotic action in RA patients (167,168).…”
Section: Melatonin In Chronic Autoimmune Disease-induced Cardiovasculmentioning
confidence: 99%
“…For example, recent evidence has demonstrated that melatonin down-regulates MMP9 activity, as well as IL-1β and TNF-α expressions in the synovial fibroblasts of patients with rheumatoid arthritis (RA) (167). Melatonin also stimulates microRNA (miR-3150a-3p) to produce anti-apoptotic action in RA patients (167,168). Both systemic lupus erythematosus (SLE) and systemic sclerosis (SS) kindle pro-inflammatory responses leading to atherogenesis and myocardial infarction (79,80), which can be targeted by melatonin (152,153,155).…”
Section: Melatonin In Chronic Autoimmune Disease-induced Cardiovasculmentioning
confidence: 99%